A Continuous Flow Device for the Purification of Semiconducting Nanoparticles by AC Dielectrophoresis. Issue 1700 (2014) - Golnabi, Rustin; Chi, Su (Ike) Chih; Farias, Stephen L.; Cammarata, Robert C.
ABSTRACT: Single-walled carbon nanotubes (SWCNTs) have attracted significant attention as building blocks for future nanoscale electronics due to their small size and unique electronic properties. However, current SWCNT production techniques generate a mixture of two types of nanotubes with divergent electrical behaviors due to structural variations. Some of the nanotubes act as metallic materials while others display semiconducting properties. This random mixture has prevented the realization of functional carbon nanotube-based nanoelectronics. Here, a method of purifying a continuous flow of semiconducting nanotubes from an initially random mixture of both metallic and semiconducting SWCNTs in suspension is presented. This purification uses A/C dielectrophoresis (DEP), and takes advantage of the large difference of the relative dielectric constants between metallic and semiconducting SWCNTs. Because of a difference in magnitude and opposite directions of a dielectrophoretic force imposed on the random SWCNT solution, metallic SWCNTs deposit onto an electrode while semiconducting SWCNTs remain in suspension [3]. A discussion of these techniques is presented, along with a dielectrophoretic force-utilized microfluidic lab-on-a-chip device that can accomplish purification of semiconducting nanoparticles at high processing rates. The effectiveness of the device is characterized using Raman spectroscopy analysis on separated samples.